Designing and implementing a novel graduate program to develop transdisciplinary leaders in urban sustainability. Issue 1 (27th January 2022) - Wallen, Megan M.; Guerra‐Lopez, Ingrid; Meroueh, Louay; Mohamed, Rayman; Sankar, Andrea; Sopory, Pradeep; Watkins, Ryan; Kashian, Donna R.
Abstract: Urban settings, where >50% of the world's population resides, are increasingly faced with environmental challenges that threaten their sustainability. Aging infrastructure, water and air pollution, and increasing recognition of environmental injustices highlight the need for professionals to employ complex scientific reasoning across disciplines where they can effectively address the multifaceted issues of urban sustainability. Here we present an innovative model for preparing the next generation of public, private, and academic leaders to address complex problems in urban sustainability. Specifically, we outline the design and implementation of an integrated, adaptable graduate training program, with the goals of science leadership, curriculum relevancy, community impact, broader applicability, establishing a career development pathway in science, technology, engineering, and mathematics (STEM) programs, and program sustainability. This program addresses human‐ecosystem challenges using a transdisciplinary approach to produce scientific products in partnership with local communities, businesses, industries, scientists, and policy makers, while providing a mechanism to understand and overcome contemporary societal and ecological challenges. Students receive rigorous training in their home disciplines, coupled with training across disciplinary lines and developmental experiences, to prepare them to communicate, collaborate, and innovate in a variety of contexts. Training success is evaluated across measurable competency domains including problem definition, research methods, communication, collaboration, and problem‐solving. After 3 years the program expanded relationships across fields and professions, successfully established 18 internship opportunities with community partners, created a new dual‐title PhD program open to students in five academic departments, and facilitated the coproduction of knowledge with external partners. This model bridges the gaps between research, education, and application, providing an integrated, rigorous graduate training program that fosters collaborative problem‐solving between STEM graduate students and the broader community of professionals conducting sustainability work in a postindustrial urban setting.